Sodium Glucose Cotransporter Type 2 Inhibitors Improve Cardiorenal Outcome of Patients With Coronary Artery Disease: A Meta-Analysis - Wei, Wen; Liu, Jin; Chen, Shiqun; Xu, Xinghao; Guo, Dachuan; He, Yibo; Huang, Zhidong; Wang, Bo; Huang, Haozhang; Li, Qiang; Chen, Jiyan; Chen, Hong; et al. (Frontiers in Endocrinology, 2022)
Objective: Sodium glucose cotransporter type 2 inhibitors (SGLT-2i) are beneficial for cardiorenal outcomes in patients with type 2 diabetes mellitus (T2DM), heart failure (HF) or chronic kidney disease (CKD). However, whether the patients with coronary artery disease (CAD) have prognostic benefit from SGLT-2i treatment has not been fully studied. The purpose of this meta‑analysis is to determine the prognostic benefit of SGLT-2i administration in CAD patients. Methods: We searched the PubMed, Embase and Cochrane Library from inception until October 15, 2021. We included randomized controlled trials (RCTs) reporting the effect of SGLT-2i on major adverse cardiovascular event (MACE), hospitalization for heart failure (HHF), cardiovascular(CV) death and cardiorenal parameters in CAD patients. Hazard ratio (HR) with 95% confidence interval (CI) and mean difference (MD) from trials were meta-analyzed using fixed-effects models. Results: Nine trials enrolling 15,301 patients with CAD were included in the analyses. Overall, SGLT2i were associated with a reduced risk of MACE (HR: 0.84; 95% CI 0.74-0.95; I2 = 0%), HHF (HR: 0.69; 95%CI 0.58-0.83; I2 = 0%) and a composite of CV death or HHF (HR: 0.78; 95% CI 0.71-0.86; I2 = 37%) in CAD patients. Compared with control group, estimated glomerular filtration rate (eGFR) level decreased less in SGLT-2i group (mean difference [MD] = -3.60, 95% CI, -1.30--5.90, p = 0.002; I2=0%). Conclusions: SGLT-2i can improve cardiorenal outcomes in CAD patients. Further RCTs and real world studies are need to investigate the effect of SGLT2i on CAD patients.